The financial toxicity of breast cancer - Ratoša, Ivica (Radiology and oncology (Ljubljana), 2025)
Background - Breast cancer is one of the most common cancers, increasingly prevalent also among working-age populations. Regardless of age, breast cancer has significant direct and indirect costs on the individuals, families and society. The aim of the research was to provide a comprehensive bibliometric analysis of the financial toxicity of breast cancer, to identify research voids and future research challenges. Materials and methods - The systematic mapping of literature relied on a multi-method approach, combining bibliometric methods with a standard review/discussion of most important contributions. The analysis employed Bibliometrics in R and VosViewer. Results - The results highlighted the key authors, journals and research topics in the investigation of the financial toxic- ity of cancer and stressed the concentration of work around several authors and journals. Conclusions -The results also revealed a lack of a comprehensive approach in the study of financial toxicity, as the literature often focuses on one or few selected aspects of financial toxicity. In addition, geographic coverage is un- even and differences in the healthcare systems represent a challenge to straightforward comparisons.
Keywords: financing; financiranje; health services; literature review; pregled literature; zdravstvo